PENILAIAN PERUBAHAN MANAJEMEN DAN KEPUASAN KERJA DOSEN TETAP PADA UNIVERSITAS BUNDA MULIA DI JAKARTA - Oktafalia Marisa (Business Management Journal, 2017)
Change Management is one of the important thing to concern if the organization wants to survive in industry. But sometimes, management needs to face the resistancy of the it change. It’s popular with the ‘resistance to change’ phrase. Works satisfaction will influenced the performance of the employe, and finaly will influenced performance of the organization. In University, lecturer performance absolutely influenced the university it’s self. Academic is a main core of University, based on that this research wants to find out, how the lecturer feels about the change management action by Bunda Mulia University. The result of the research will provide a basic information about what lecturer feel and how that’s change affected their performances. Hopefully this research could provided a comprehensif data to develop any research in the future.Key WordsChange Management, Work Satisfaction, Lecturers